MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Mursyidah, Azizah; Anwar, Miftakhul; Wildan, Zaenal (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
The introduction of Islamic commercial banks in rural areas plays an important role in increasing financial inclusion and supporting community welfare with sharia-compliant financial services. This community service article aims to programme an effective approach to introduce Islamic banking to rural communities who often do not have adequate access to formal banking. The method used involves a social approach through community leaders, youth, education tailored to the language and needs of the local community as well as groups or organisations such as recitation. The community service activity aims to increase a thorough and effective understanding to the community of Ciaruteun Ilir Village, Cibungbulang District, Bogor Regency, regarding Islamic banking, especially Islamic commercial banks. The introduction of Islamic banking activities to the community is given with the aim of educating and opening up insights about Islamic banks. The result of this service activity is that the people of Ciaruteun Ilir Village have knowledge about Islamic commercial banks and have the desire to save or invest in Islamic banks. This service is expected to be a reference for the development of Islamic banking strategies in rural areas, especially in Indonesia.